Distinctions Between Self-Report and Performance-Based Measures of Physical Function in Older Patients Prior to Chemotherapy. Issue 6 (November 2021) - Torstveit, Ann Helen; Løyland, Borghild; Grov, Ellen Karine; Guren, Marianne; Paul, Steven M.; Ritchie, Christine; Vistad, Ingvild; Miaskowski, Christine; Utne, Inger
Abstract : Background: The maintenance of physical function (PF) is an extremely important outcome for elderly people. Objective: The aims of this study were to identify differences in the subjective and objective measures of PF between younger older adults (YOAs, 60-69 years of age) and older adults (OA, ≥70 years of age), to compare the PF scores with age-matched samples from the general population, and to evaluate for associations between the subjective and objective measures of PF. Methods: Patients (n = 139) were assessed using subjective (ie, European Organization for Research and Treatment of Cancer Core Quality-of-Life Questionnaire) and objective (ie, Short Physical Performance Battery [SPPB]) measures prior to chemotherapy (CTX). Data were analyzed using parametric and nonparametric tests. Results: No differences were found between the 2 age groups in any of the subjective or objective measures of PF. Compared with the age-matched general population, both YOAs and OAs had significantly lower scores in both measures of PF. Large effect sizes were found for differences in European Organization for Research and Treatment of Cancer Core Quality-of-Life Questionnaire role function, SPPB balance, and SPPB total scores between the YOA group and the age-matched general population samples. Correlations between the subjective and objective measures were low. Conclusions: Older patients with cancer have lower PF than their age-matched general population prior to CTX. Longitudinal studies are warranted to evaluate for changes in PF during and following CTX. Implications for Practice: Nurses need to perform routine assessments of PF in older oncology patients prior to CTX. Our findings suggest that SPPB gait speed may be a useful screening measure for PF in older patients. Abstract : Supplemental digital content is available in the text.